Notas acerca del desequilibrio espacial de las disponibilidades hídricas en la Comunidad Valenciana - Bru Ronda, Concepción (Investigaciones Geográficas, 1987)
Water problems in the Comunity of Valencia with the existence of shortages in some areas is a fact that has been detected since long ago, this matter is marked before hand by the climatological conditions. The outstanding increase of water demand during the second half of the Century has intensified the unbalance between resources and demands. Throughout history several initiatives have tried to reduce these problems. At present the socioeconomic and technological changes call for a reorganization of the systems of water economy which should be based, in synthesis in a wholesome effort, national, integral and communitary.